Incidence of Heparin-Induced Thrombocytopenia in Patients With Newly Implanted Mechanical Circulatory Support Devices. Issue 5 (May 2022) - To, Long; Attar, Dana; Lines, Brittany; McCarty, Melissa; Nemeh, Hassan; Lopez-Plaza, Ileana; Smith, Zachary; Coba, Victor; Lekura, Jona
Background: Heparin exposure and device-related thrombocytopenia complicate the diagnosis of heparin-induced thrombocytopenia (HIT) in patients receiving mechanical circulatory support (MCS). To improve anticoagulation management for patients with newly implanted MCS devices, incidence of confirmed HIT needs to be further characterized. Objectives: The purpose of this study is to describe the incidence of HIT and clinical utility of the 4Ts score in patients with newly implanted MCS devices. Methods: This is a retrospective analysis of MCS patients receiving unfractionated heparin from 2014 to 2017. The primary end point was incidence of laboratory-confirmed HIT. Strong positive, likely positive, low probability, and negative HIT categories were established based on heparin-induced platelet antibody (HIPA) and serotonin release assay (SRA). Secondary end points include characterization of platelet trends, argatroban use, incidence of HIT among each of the MCS devices, and utility of 4Ts score. Results: A total of 342 patient encounters met inclusion criteria, of which 68 HIPA tests and 25 SRAs were ordered. The incidence of HIT was 0.88% (3/342) and 4.4% (3/68) in patients with suspected HIT. Of the 68 HIPA tests, 3 (4.4%) were considered strong positive and 3 of the 25 SRAs were positive. Median 4Ts score was 4 [2.5-4] and optical density 0.19 [0.11-0.54]. The positive predictive value for the 4Ts score was 0.15 (CI = 0.03-0.46) and negative predictive value, 0.93 (CI = 0.82-0.98). Conclusion and Relevance: HIT occurs infrequently with newly implanted MCS devices. The 4Ts score appears to have a high negative predictive value for ruling out HIT.